SOSIALISASI PEMILIHAN DAN PENGGUNAAN KOSMETIK CREAM PEMUTIH WAJAH YANG AMAN PADA SANTRIWATI PESANTREN MODERN FAJRUL IMAN PATUMBAK DELI SERDANG SUMATERA UTARA - Ahmad Purnawarman Faisal; Riza Fahlevi Wakidi; Masrah Masrah (Jurnal Abdi Masyarakat Kita, 2021)
In this technological era, it is easy to get information about the facial whitening cream products, various information media such as television, newspapers, magazines and social media which are booming among women, especially school-age teenagers. With the ease of this information, buyers often ignore the quality and safety of the cosmetics themselves, many cosmetics contain harmful bleaching agents such as mercury and hydroquinone. The purpose of this Community Service is to find out the description of knowledge and socialize the Safe Selection and Use of Face Whitening Cream for students at the Fajrul Iman Patumbak Islamic Boarding School. The method used in this community service is lectures and questions and answers about the Selection and Use of Safe Face Whitening Cream Cosmetics. From the results of community service before the counseling was held on the Selection and Use of Safe Face Whitening Cream Cosmetics at Fajrul Iman Modern Islamic Boarding School students, it was found that the knowledge category was quite good (23.3%) in the good category (76.7%), and after the counseling was carried out the category was obtained. good knowledge becomes (100%), there is an increase in knowledge of good category as much as 23.3%. So that the Fajrul Iman Islamic boarding school students as respondents already understand the Selection and Use of Safe Face Whitening Creams